Lestrimelitta chacoana Roig-Alsina, 2010 (Meliponini, Apidae) in a Semideciduous Atlantic Forest, Southern Brazil - Colombelli , Julia Agostini; Ojeda, Yoan Delky Ibañez; Schühli, Guilherme Schnell e; Zanella, Fernando Cesar Vieira (EntomoBrasilis, 2024)
The species of the cleptobiotic bee genus Lestrimelitta Friese, 1903 (Hymenoptera: Apidae) are generally known as a menace to Meliponiculture and Apiculture, that is why it is common to observe recommendations to beekeepers to avoid the proximity of their meliponaries with any Lestrimelitta hives. So, besides other anthropic pressures, the growth of beekeeping may represent a particular threat to its species. In this note we address the distribution of three species recorded in the triple border region of Argentina, Paraguay, and Brazil. One of these species, Lestrimelitta chacoana Roig-Alsina, 2010 (Hymenoptera: Apidae), previously described from the Argentinian Dry Chaco, is recorded for the Semideciduous Atlantic Forest in Southern Brazil where it was already expected to be found due to its previous record in a contiguous forest type in Northeastern Argentina. A discussion about the characters to differentiate it from two other species is made.